2015
DOI: 10.1088/0964-1726/24/3/035026
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of magnetorheological elastomers with coated particles

Abstract: Iron particle coating can improve the behavior of magnetorheological elastomers (MREs) by inhibiting iron particle rusting; however, such a process can change physical properties of MREs such as oxidation resistance, shear modulus, and stiffness change due to an applied magnetic field. In this study, MRE samples are fabricated with regular and polymerized iron particles. To investigate the possibility and extent of these changes, polymerized particle MRE samples are made using a combination of reversible addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…This effect becomes stronger in nanocomposites because of the increased surface interaction energy between smaller inclusions separated by smaller distances. The use of surface‐functionalized fillers [ 41,96,107,117,128–131 ] to build a matrix‐free nanocomposite, or tailoring the dispersion of nanoparticles by designing the chain architecture [ 132 ] can solve this aggregation issue. Nevertheless, the scarcity of permittivity data prevents a reasonable testing of the mixing rules for such nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect becomes stronger in nanocomposites because of the increased surface interaction energy between smaller inclusions separated by smaller distances. The use of surface‐functionalized fillers [ 41,96,107,117,128–131 ] to build a matrix‐free nanocomposite, or tailoring the dispersion of nanoparticles by designing the chain architecture [ 132 ] can solve this aggregation issue. Nevertheless, the scarcity of permittivity data prevents a reasonable testing of the mixing rules for such nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Homogeneous distributions of particles in experimental studies can be achieved by the functionalization of their surfaces. [ 41,96,107,117,128–131 ] In ref. [132], the influence of polymer chain architecture on nanoparticle dispersion and the mechanical behavior of the polymer nanocomposite are examined in coarse‐grained simulations.…”
Section: Calculation Of the Nanocomposite Permittivity From The Distrmentioning
confidence: 99%
“…It is well known that the dispersibility of magnetic particles strongly influences the magnetic-field response. The dispersibility of magnetic particles can be improved on a micro- or nano-scale, by the surface modification of magnetic particles [15,16,17,18], resulting in the giant magnetorheological response. For example, a magnetic elastomer with nanoscale homogeneity shows a large increase in Young’s modulus at relatively weak magnetic fields [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies to overcome this problem by fabricating the magnetic particles being surface-modified with organic or inorganic materials have been reported by using proper compatibilizers [ 74 , 75 , 76 , 77 , 78 , 79 ]. Li et al [ 75 ] prepared core-shell structured poly(methyl methacrylate) (PMMA)-coated CI particles to investigate the effect of particle coating on the dynamic properties of the MR elastomers with PMMA matrix.…”
Section: Magnetorheological (Mr) Elastomermentioning
confidence: 99%
“…It was found that the MR elastomers with surface-coated iron particles possessed superior mechanical properties with respect to the oxidation stability test. Behrooz et al [ 77 ] prepared poly(tetrafluoropropyl methacrylate) (PTFPMA)-coated iron particles utilizing a combination of reversible addition fragmentation chain transfer polymerization and click chemistry techniques. The PTFPMA-coated iron particles did not show a significant change in the shear modulus of the MR elastomers, but the loss of shear modulus due to oxidation was reduced.…”
Section: Magnetorheological (Mr) Elastomermentioning
confidence: 99%